A 6-year trends analysis of infections after revision total hip arthroplasty - Gold, Peter A.; Garbarino, Luke J.; Sodhi, Nipun; Anis, Hiba K.; Ehiorobo, Joseph O.; Kurtz, Steven M.; Danoff, Jonathan R.; Rasquinha, Vijay J.; Higuera, Carlos A.; Mont, Michael A. (Annals of Translational Medicine; Vol 7, No 4 (February 27, 2019): Annals of Translational Medicine (Focus on “Lower Extremity Arthroplasty”), 2019)
Background: Substantial efforts have been made to reduce the risk of infection after total hip arthroplasty (THA), including pre-operative patient optimization, skin preparation with alcohol-based solutions, perioperative antibiotics, and minimizing wound drainage with novel sutures and dressings. While these approaches have been effective in primary THA, their effects on revision THA to improve surgical site infection (SSI) rates are less clear. Therefore, the purpose of this study was to identify the annual rates and trends of: (I) overall; (II) deep; and (III) superficial SSIs following revision THA using the most recent results (2011 to 2016) from a large, nationwide database. Methods: The National Surgical Quality Improvement Program (NSQIP) database was queried for all revision THA cases (CPT code 27134) between 2011 and 2016, yielding 8,562 cases. A steady increase in the total number of revision THA cases was observed from 2011 to 2016 (750 vs. 1,951, 260%). Cases with reported superficial and/or deep SSI were analyzed separately and then combined to evaluate overall SSI rates. The infection incidence for each year was calculated. After an overall 6-year correlation and trends analysis, univariate analysis was performed to compare the most recent year, 2016, with each of the preceding 5 years. Additionally, percent differences between 2016 and each previous year were calculated to evaluate rate changes. Pearson correlation coefficients and chi-squared tests were used to determine correlation and statistical significance which was maintained at a P value less than 0.05. Results: There were 217 cases out of 8,562 (2.53% of all cases) complicated by any SSI. Overall, there was an inverse correlation between combined SSI rate and year, however, this was not statistically significant (P>0.05). The lowest incidence was in 2016 (n=41, 2.10%), while the highest incidence was in 2014 (n=45, 2.86%). The combined SSI rate in 2016 decreased by 22% when compared to 2015 (2.10% vs. 2.69%, P>0.05). A larger, 27% decrease in rate was found between 2016 and 2014 (2.10% vs. 2.86%, P>0.05). For deep SSI, there was an inverse correlation between rate and year of surgery, however, this was not statistically significant (P>0.05). The deep SSI incidence over the 5 years was 1.38% (118 out of 8,562 cases). There was a 35% decrease in deep SSI rate from 2016 to 2015 (0.92% vs. 1.43%, P>0.05). A larger, 53% decrease, was seen between 2016 and 2014 (0.92% vs. 1.04%, P0.05). In this 6-year period, 99 cases out of 8,562 were complicated by a superficial SSI; an incidence of 1.16%. The lowest incidence occurred in 2014 (n=14, 0.89%), while 2012 had the highest incidence (n=17, 1.61%). The rate in 2016 decreased by 6% when compared to 2015 (1.18% vs. 1.07%, P>0.05). A larger, 27% decrease in rate was observed between 2016 and 2012 (1.18% vs. 1.61%, P>0.05). Conclusions: Revision total hip arthroplasties exhibited a trend towards decreasing overall SSI nationwide between 2011 and 2016. Deep SSI rates had marked improvements, specifically between 2014 and 2016. This trend indicates some benefit from pre- and post-operative infection preventative strategies, but importantly, indicates continued room for improvement. Due to the potentially devastating complications associated with infection in revision THAs, further research is required to identify revision-specific strategies to lower the rates of SSIs.